New Wave of Marketing In Politics Case Study: Success of Millennials In DPRD DKI Jakarta In 2019 - 2024 Legislative Election - Fauzan Fadel; Yudo Anggoro (Syntax Literate, 2022)
An interesting phenomenon occurred in a remarkably effective and efficient shift in campaign strategy carried out by young millennial parliamentarians who won the 2019 DKI Jakarta legislative elections by controlling the parliamentary seats of the DPRD DKI Jakarta by 30%. Millennials are the majority community group of DKI Jakarta residents who actively use social media. The young generation of DKI Jakarta millennials is the target of Potential Market (Voters) by young legislative candidates as Segmentation, Targeting, and Positioning Marketing in conveying the concept of their work program to win the election and win the hearts of the grassroots community in the 2019 DKI Jakarta Legislative Election and be able to beat the senior incumbent politician with experience in politics. The research methodology used with a qualitative and quantitative research approach, which carries out a primary research approach, by distributing questionnaires using random sampling techniques. Furthermore, this research also conducted direct interviews with young legislators who won the 2019-2024 Legislative Election. The quantitative research such as external analysis and internal research by carrying out approaches through Benchmarking analysis and PESTEL Analysis. As well as internal analysis with the C12 New Wave Marketing approach and VRIO Analysis. From the results of studies that have been carried out, it is indicated that the implementation of Strategic New Wave Marketing by implementing and formulating the 12C implementation that prioritizes New Wave Value can form a distinctive personal brand of a politician who can form bonds with grassroots communities in their chosen area.